Dutch Disease Effect of Oil and Natural Gas on the Economy of Azerbaijan Republic - Mammadzada, Kamil; Šíma, Ondřej; Metrah, Samy; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2021)
In this study, the Dutch disease, the main sectors of the Azerbaijani economy and the impact of the Dutch disease on the economy of Azerbaijan were examined. Thanks to the dense capital structure of the oil sector, the effect of resource allocation, which had the main impact on the Dutch disease, did not materialize. On the other hand, the effect of expenditures appeared as an increase in public expenditures in the Azerbaijani economy. At the same time, the economy of Azerbaijan is heavily dependent on the oil sector. But oil can also quickly disappear if used to meet its short-term needs. Naturally, it is a great advantage if the oil is used reasonably and to secure the long-term interests of the state. The experience of many oil countries shows that besides solving many social problems, a country can also pave the way for a serious economic decline. From this point of view, if the increase in oil profits seems positive, then its rational use is one of the most important issues. This study reflects the spending direction and investment mechanisms of the State Oil Fund. Various scenarios for investment and their pros and cons were examined.
Vedoucí práce: Ondřej Šíma
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses